AIDS in men in the city of São Paulo, 1980-2012: spatial and space-time analysis - Alessandra Cristina Guedes Pellini; Francisco Chiaravalloti-Neto; Dirce Maria Trevisan Zanetta (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVES: To identify spatial and space-time clusters with high incidence rates of AIDS in men living in the city of São Paulo since the first case of the disease in 1980. METHODS: HIV/AIDS notifications were obtained from the Notifiable Diseases Information System (57,440 men) between January 1980 and June 2012. The cases were geocoded by residence address; then analyses of purely spatial, space-time and spatial variation in temporal trends were performed for three sets of data: total cases of AIDS in men aged 13 years or older, men aged 50 years or older, and deaths from AIDS. RESULTS: It was possible to geocode a significant proportion of AIDS cases (93.7%). In the purely spatial scanning analysis, considering the entire period evaluated, the AIDS epidemic in men presented an important spatial concentration in the Center and in contiguous areas of the North, Southeast and West regions of the municipality, regardless of age group and evolution to death (relative risks between 1.22 and 5.90). Considering space and time simultaneously, several clusters were found, spread throughout all regions of the municipality (relative risks between 1.44 and 8.61). In the analysis of spatial variation in temporal trends, the clusters in the most peripheral regions presented a higher annual percentage increase in disease rates (up to 7.58%), denoting the tendency of "peripherization" of the epidemic in men in the city of São Paulo. CONCLUSIONS: This study allowed the detection of geographic clusters of high risk for AIDS in men, pointing to priority areas in the municipality, both for programmatic actions and to guide other studies.